Disparities in SARS-CoV-2 Testing for Hispanic/Latino Populations: An Analysis of State-Published Demographic Data. Issue 4 (9th July 2022) - Pond, Emily N.; Rutkow, Lainie; Blauer, Beth; Aliseda Alonso, Angel; Bertran de Lis, Sara; Nuzzo, Jennifer B.
Abstract : Racial and ethnic minorities in the United States have been disproportionately affected by the COVID-19 pandemic, experiencing increased risk of infection, hospitalization, and death. In this study, we sought to examine race- and ethnicity-based differences in SARS-CoV-2 testing. We used publicly available US state dashboards to extract demographic data for COVID-19 cases and tests. Poisson regression models were used to model the effect of race and ethnicity on the number of SARS-CoV-2 tests performed per case. In total, just 8 states reported testing data by race and ethnicity. In regression models, race and ethnicity was a significant predictor of testing rate per case. In all states, Hispanic/Latino patients had a significantly lower testing rate than their non-Hispanic/Latino counterparts, with an incident rate ratio varying from 0.45 to 0.81, depending on the state and referent race category. These results suggest disparities in testing access among Hispanic/Latino individuals, who are already at a disproportionate risk for infection and severe outcomes.